A randomized, double-blind trial comparing pegylated interferon alfa-2b to interferon alfa-2b as initial treatment for chronic hepatitis C - Lindsay, Karen L.; Trepo, Christian; Heintges, Tobias; Shiffman, Mitchell L.; Gordon, Stuart C.; Hoefs, John C.; Schiff, Eugene R.; Goodman, Zachary D.; Laughlin, Mark; Yao, Ruji; Albrecht, Janice K. (Hepatology (Baltimore, Md.), 2001)
This international, randomized, active-controlled, parallel-group, double-blind dose-finding study compared peginterferon alfa-2b (PegIntron™) to interferon alfa-2b for the initial treatment of compensated chronic hepatitis C. We randomly assigned 1,219 subjects to receive either the standard three-times-weekly (TIW) interferon alfa-2b dose (3 MIU) or the once-weekly (QW) peginterferon alfa-2b (0.5, 1.0, or 1.5 μg/kg). Subjects were treated for 48 weeks and then followed for an additional 24 weeks. All 3 peginterferon alfa-2b doses significantly (P ≤ .042) improved virologic response rates (loss of detectable serum HCV RNA) after treatment and after follow-up, as compared with interferon alfa-2b. Unlike the end-of-treatment virologic response, the sustained virologic response rate was not dose-related above 1.0 μg/kg peginterferon alfa-2b because of a higher relapse rate among patients treated with 1.5 μg/kg peginterferon alfa-2b, particularly among patients infected with genotype 1. All 3 peginterferon alfa-2b doses decreased liver inflammation to a greater extent than did interferon alfa-2b, particularly in subjects with sustained responses. No new adverse events were reported, and the majority of adverse events and changes in laboratory values were mild or moderate. In conclusion, peginterferon alfa-2b maintained (0.5 μg/kg) or surpassed (1.0, 1.5 μg/kg) the clinical efficacy of interferon alfa-2b while preserving its safety profile. The higher rate of virologic response during treatment with 1.5 μg/kg peginterferon alfa-2b in patients infected with genotype 1 and high viral levels warrants further evaluation. (HEPATOLOGY 2001;34:395-403.)